Evaluation on the use of electronic information resources by business students in Singapore Polytechnic. - Rindra Mokhtar Ramli. (2008)
This study focused on the usage of electronic information resources by students from School of Business, Singapore Polytechnic. The survey method of questionnaire was used for data collection. Study revealed several interesting findings.